Therapeutic trial of doxycyclin plus ivermectin for the treatment of Brugia malayi naturally infected cats - Ladawan Khowawisetsut (2018)
© 2017 Elsevier B.V. Lymphatic filariasis (LF) is one of the neglected tropical diseases which causes permanent and long term disability worldwide. LF is caused by filarial nematode parasites, i.e. Wuchereria bancrofti, Brugia malayi, and B. timori. All available antifilarial drugs currently being used have shown a limited adulticidal activity. Discoveries of endosymbiont rickettsia-like bacterium, Wolbachia in filarial nematodes provided a novel approach for antibiotic use in eradication of filarial diseases. The earlier studies revealed the macrofilaricidal efficacy of doxycycline against filarial nematodes. Chemotherapeutic efficiency of doxycycline has been studied against many filarial parasites, but there are still no therapeutic trials of the drug regimens for B. malayi treatment in naturally infected cats. Thus, this study would be the first attempt to study the efficiency of doxycycline (DOXY) alone or in combination with ivermectin (IVM) for treatment of B. malayi in naturally infected cats. A total of 26 B. malayi-infected cats in the endemic areas were recruited and divided into 3 groups, receiving different treatment regimens; a single dose of ivermectin only (IVM), doxycycline only (DOXY) and a combination of ivermectin and doxycycline (DOXY-IVM). The efficacy of each therapatic regimen was evaluated by detecting the presence of microfilaria using parasitological and molecular techniques monthly up to 2 years after starting the treatment. The IVM treated group had a significant rapid reduction of microfilariae in the first month; however, recurrence of microfilaraemia was observed in some cats. By contrast, the DOXY and DOXY-IVM groups showed a better result with a gradual decrease in microfilariae with no recurrence. These 2 groups were not only virtually deprived of infection but also sustained the sterility of infection through the course of study. These results revealed the advantages of using in B. malayi treatment in cats. Doxycycline showed to have both microfilaricidal and adulticidal effects on lymphatic filariae which maintained the long-term response to control of B. malayi infection in cats.